Lunar Science - Chemin, Yann H. (IntechOpen, 2019)
Lunar science is in the middle of a small revolution, with now many new countries sending orbiters, landers, and even sample return missions to the moon. Additionally, both governments and private companies are now more and more considering the moon as a base for solar system exploration. With such an increase in attention, lunar science is now encompassing several unified dimensions. The first is the science of the moon itself, its origin, evolution, and inner composition. The second is how humans can live on the moon, covering biology and in general the logistics of surviving there, including surface mapping and in-situ resource utilization.